การทำนิติกรรมและมรดกของพระภิกษุที่เกี่ยวข้องกับสินสมรส - จักรพัฒน์ โรจน์อารยานนท์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
It was enacted in the early Thai Family Law that spouses must separate themselves when the husband ordained in Buddhist religion. However, according to the present Civil and Commercial Code article 1501, ordination is not considered as the ending of spouses’ relationship, he still holds husband status and all legal rights. He also has to manage their marital properties occasionally through juristic acts which might receive the payment and it is against Buddhist disciplines. However, the judgment of the Supreme Court no.3773/2538 recognised the monks’ right to execute juristic acts and receive the payment by giving reasons that "Juristic act was bound due to the fact that it was not contrary to public order or good moral". Obviously, the judgment were contradicted to the Buddhist disciplines.To define the meaning of ‘the property the monk got during his priesthood’, according to article 1623, it relates to all kinds of properties that he acquired in every way whether that property will be in the temple area or not. The precedent of the Supreme Court confirmed that the land belongs to temple will be turned into the monastery estate immediately since the monk passes away. According to the Buddhist Monk Act, B.E. 2505, the monastery estate is not under the case enforcement. Moreover, the Department of Lands has set the rule that the land which the husband got during his priesthood, in every case, is not considered as the marital properties. And all the land will be turned into the ownership of the temple when he passes away in which the wife cannot share any part of it. However, the Family Law has not been enacted that the ordination does end the marital status. The property that the husband obtains while he is a commoner is considered as the marital property which the wife can request the share. Furthermore, if the monk had been in debt related to that property before he passed away, and if that property is the land, it will cause trouble to pay off the debt to the creditor. The ownership transfer of monastery estate can only be done by the Act legislation. If the land is transferred to the creditor by the contract, such transfer of the ownership of is voided because it is against the Buddhist Monk Act, B.E. 2505. Finally, the legal opinion of the Council of State bill drafting committee on article 1623, chapter VI, succession, of the Civil and Commercial Code, is that this article do not intend to include ‘monastery estate’ in ‘property of the monastery’. Moreover, the judgment of the Supreme Court no.439/2479, on article 1623 considers the ‘property of the monastery’ as the property that after paying all debts to the creditor of the monk who passes away. Besides the judgment of the Supreme Court no. 952/2507 declared that the marital property must be divided and given to the wife before transferring the property to the temple, and this division must not go against the real purpose of Buddhist Monk Act, B.E. 2505. All in all, the writer would like to recommend the interpretation of the law that complies with the real intention of law, in order to give justice to everyone who involves in the case.